Test of Anti-inflammatory Effectiveness of Ethanol Extract of Green Betel Leaves (Piper betle L.) on White Rats (Rattus norvegicus) Induced with Formaldehyde - Turangan, Pricilia Dona; Bodhi, Widdhi; Lebang, Julianri Sari (PHARMACON, 2024)
Green betel leaves are known to contain tannin and flavonoid compounds which have the potential to provide anti-inflammatory effects. This study aims to determine the effect of ethanol extract of green betel leaves with several variations as an anti-inflammatory on edema of white rat’s paw induced by 1% formaldehyde given intraplantarly. Animals that had been induced by formaldehyde were given ethanol extract of green betel leaves after 30 minute,then the diameter of the rat's paw edema was measured using a caliper. The results showed that the negative control experienced an increase in the percentage of inflammation by 77.87% which was significantly different from the positive control, while the extract test group with doses of 25 mg/200gBW, 30 mg/200gBW, and 40 mg/200gBW could provide a decrease in the percentage value of inflammation respectively. - respectively 34.07%, 21.76%, and 4.80% and all three were not significantly different from the positive control (Asymptotic significance≥0.05). Based on research results, ethanol extract of green betel leaves can provide anti-inflammatory effects at a dose of 40 mg/200gBW as the best dose in reducing the diameter of rat paw edema.